Risk Factors for 30-Day Non-Neurological Morbidity and Cerebrospinal Fluid Leak in Patients Undergoing Surgery for Vestibular Schwannoma - Gelfand, Yaroslav (J Neurol Surg B Skull Base, 2020)
Introduction  We analyzed perioperative risk factors for morbidity and mortality for the patients undergoing surgical intervention for vestibular schwannoma along with rates of cerebrospinal fluid (CSF) leaks that required surgery. Materials and Methods  Patients undergoing surgery vestibular schwannoma were identified in the American College of Surgeons National Surgical Quality Improvement Program database from 2012 to 2016 using current procedural terminology (CPT) codes for posterior fossa surgical approaches and International Classification of Diseases 9th revision (ICD 9) and ICD 10 codes for peripheral nerve sheath tumor. Preoperative laboratories, comorbidities, and operative times were analyzed along with CSF leaks and unplanned returns to the operating room. Results  Nine-hundred ninety-three patients fit the inclusion criteria. Average age was 51, 41% were male, and 58% were female. Mortality within 30 days of the operation was very low at 0.4%, complications were 7% with infection being the most common at 2.3%, and unplanned reoperations happened in 7.4% of the cases. Dependent functional status (odds ratio [OR]: 5.7, 95% confidence interval [CI]: 1.9–16.6, p  = 0.001), preoperative anemia (OR: 2.4, 95% CI: 1.2–4.5, p  = 0.009), and operative time over 8 hours (OR: 1.9, 95% CI: 1.1–3.4, p  = 0.017) were the only significant predictors of perioperative complications. CSF leak postoperatively occurred in 37 patients (3.7%). Reoperation for CSF leak was necessary in 56.3% of the cases. Operative time over 8 hours was the only independent significant predictor of postoperative CSF leak (OR: 2.2, 95% CI: 1.1–4.3, p  = 0.028). Conclusion  Dependent functional status preoperatively, preoperative anemia, and duration of surgery over 8 hours are the greatest predictors of complications in the 30-day postoperative period.